THE ECONOMIC SIGNIFICANCE OF RECENT PRICE LEGISLATION. - Griffin, C. E. (The Accounting Review, 1939)
Abstract The price legislation referred to in this article includes the Robinson-Patman Act, the various state resale-price-maintenance laws together with the Miller-Tydlings amendment, and the minimum-price laws, which have recently enacted by the U.S. government. Some of the features which these laws have in common have been suggested. These laws impinge upon prices in apparently different ways, the first deals with relative prices paid by retailers, the second with prices relative and absolute charged by retailers for identical branded goods, and the third group with prices charged by retailers on any and all goods relative to the costs of those goods. To discover the real significance of these laws, one must be concerned with the identity of sponsors, their motives, and the state of mind of the public and the legislators who approved them than with the defenses that can be offered for them. The broader significance of recent price laws is that they are antichain-store and antiprice-cutting laws. As such, they are designed to protect the general run of independent merchants from the competition of those who threaten the existing order.